Community-Based Business Planning for Transgender Women’s Economic Empowerment - Robertus Adi Nugroho; Thyophoida W.S. Panjaitan; Evelyn Joyce Emmanuella (Universitas Nurul Jadid, 2025)
This community engagement program was implemented by a team of lecturers and students from Darma Cendika Catholic University in collaboration with PERWAKOS (the Surabaya Association of Transgender Women). The program aimed to promote economic empowerment among transgender women by identifying entrepreneurial potential, examining structural barriers, and formulating realistic recommendations for sustainable livelihood development. The findings indicate that all participants expressed strong interest in engaging in small-scale entrepreneurial activities, particularly in the beauty, retail, and culinary sectors. However, this interest was constrained by several challenges, including limited financial literacy, lack of prior business experience, low levels of intra-community trust, and persistent social stigma. The program produced several tangible outputs, including a documented needs assessment involving 20 community members, the identification of priority business sectors, and consensus-based recommendations for future capacity-building initiatives. Based on these findings, the program recommends that subsequent community engagement efforts prioritize basic financial management training, structured business plan development, and psychosocial support to enhance self-confidence and collective commitment. In addition, facilitating access to inclusive microfinance schemes and strengthening partnerships with supportive institutions are essential to addressing structural barriers. Overall, this program demonstrates that context-sensitive community engagement can serve as an effective foundation for fostering economic self-reliance and organizational strengthening within marginalized transgender communities.